Early foreland deformation of the Fuegian Andes (Argentina): Constraints from the strain analysis of Upper Cretaceous-Danian sedimentary rocks - Torres Carbonell, Pablo Juan; Dimieri, Luis Vicente; Martinioni, Daniel Roberto (Journal of Structural Geology)
This contribution addresses new structural data from Upper Cretaceous-Danian sedimentary rocks of the Fuegian Andes orogenic front in Argentina. The structures studied, called D0 , were formed during the early foreland deformation of the orogen, in the Late Cretaceous-Danian, in times when South America and Antarctica were still connected. The strain analysis of these structures indicates that deformation occurred at upper-crustal depths, and was characterized by flexural folding accompanied by formation of pressure-solution tectonic foliations in zones of higher strain. Deformation intensities increase toward the hinterland and with depth. The history of deformation involved progression from layer-parallel shortening to folding above a detachment, and further formation of a forward-propagating thrust wedge. Layer-parallel shortening and incipient folding recorded in Maastrichtian-Danian rocks indicate the leading edge of D0 deformation. Non-coaxial finite strain orientations were involved during formation of D0 structures along the Fuegian Andes front. These finite strain orientations cannot be explained with the SW-NE regional contraction usually assumed to have driven Andean deformation in this region; alternatively, we consider that N-S contraction combined with buttressing against the cratonic foreland comprise a more suitable interpretation for D0 and younger deformation. Fil: Torres Carbonell, Pablo Juan. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Dimieri, Luis Vicente. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca. Instituto Geológico del Sur. Universidad Nacional del Sur. Departamento de Geología. Instituto Geológico del Sur; Argentina Fil: Martinioni, Daniel Roberto. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina